Environmental degradation results in contrasting changes in the assembly processes of stream bacterial and fungal communities. Issue 9 (11th April 2017) - Mykrä, Heikki; Tolkkinen, Mikko; Heino, Jani
Abstract : Environmental degradation may have strong effects on community assembly processes. We examined the assembly of bacterial and fungal communities in anthropogenically altered and near‐pristine streams. Using pyrosequencing of bacterial and fungal DNA from decomposed alder Alnus incana leaves, we specifically examined if environmental degradation deterministically decreases or increases the compositional turnover of bacterial and fungal communities. Our results showed that near‐pristine streams and anthropogenically altered streams supported distinct fungal and bacterial communities. The mechanisms assembling these communities were different in near‐pristine and altered environments. Environmental disturbance homogenized bacterial communities, whereas fungal communities were more dissimilar in disturbed sites than in near‐pristine sites. Compositional variation of both bacteria and fungi was related to water chemistry variables in disturbed sites, further implying the influence of environmental degradation on community assembly. Bacterial and fungal communities in near‐pristine streams were weakly controlled by environmental factors, suggesting that the relative importance of niche‐based versus neutral processes in assembling microbial communities may strongly depend on the spatial scale and local environmental context. Our results thus suggest that environmental degradation may strongly affect the composition and β‐diversity of stream microbial communities colonizing leaf litter, and that the direction of the change can be different between bacteria and fungi. A better understanding of the environmental tolerances of microbes and the mechanisms assembling microbial communities in natural environmental settings is needed to predict how environmental alteration is likely to affect microbial communities.